Tautomeric GU pairs within the molecular ribosomal grip and fidelity of decoding in bacteria. Issue 14 (21st June 2018) - Rozov, Alexey; Wolff, Philippe; Grosjean, Henri; Yusupov, Marat; Yusupova, Gulnara; Westhof, Eric
Abstract: We report new crystallographic structures of Thermus thermophilus ribosomes complexed with long mRNAs and native Escherichia coli tRNAs. They complete the full set of combinations of Watson–Crick GC and miscoding GU pairs at the first two positions of the codon–anticodon duplex in ribosome functional complexes. Within the tight decoding center, miscoding GU pairs occur, in all combinations, with a non-wobble geometry structurally indistinguishable from classical coding Watson–Crick pairs at the same first two positions. The contacts with the ribosomal grip surrounding the decoding center are all quasi-identical, except in the crowded environment of the amino group of a guanosine at the second position; in which case a G in the codons may be preferred. In vivo experimental data show that the translational errors due to miscoding by GU pairs at the first two positions are the most frequently encountered ones, especially at the second position and with a G on the codon. Such preferred miscodings involve a switch from an A-U to a GU pair in the tRNA/mRNA complex and very rarely from a G = C to a GU pair. It is concluded that the frequencies of such occurrences are only weakly affected by the codon/anticodon structures but depend mainly on the stability and lifetime of the complex, the modifications present in the anticodon loop, especially those at positions 34 and 37, in addition to the relative concentration of cognate/near-cognate tRNA species present in the cellular tRNA pool.